Localization and Identification of Thrombin and Plasminogen Activator Activities in Model Human Thrombi by in situ Zymography - Mutch, Nicola J.; Moir, Elaine; Robbie, Linda A.; Berry, Susan H.; Bennett, Bruce; Booth, Nuala A. (Thrombosis and Haemostasis, 2002)
Human thrombi vary in their susceptibility to lysis and this is clinically important. Several potential contributory factors were examined in this study by using model thrombi, created under flow; these provide a robust, reproducible and easily-manipulated system. Here we identify the plasminogen activators (PA) active in model thrombi of known age and define the cellular and plasma contribution to activity in different areas. The cell-rich head of model thrombi had strong thrombin and PA activity, with coagulant activity also at the tail. Thrombin activity decreased as model thrombi were aged. PA activity in the thrombus head also decreased on ageing of thrombi but activity emerged around the thrombi, including the tail. Activity in the head of fresh model thrombi was primarily due to uPA, with some contribution from tPA. Experiments with thrombi prepared from platelet-rich plasma and added leucocytes showed that uPA activity at the head of fresh thrombi was derived from PMN. Older thrombi had tPA activity around the tail of the thrombus; this activity occurred in the absence of cells. This study highlights the importance of PMN-derived uPA activity in the lysis of fresh thrombi, with activity originating in the leucocyte-rich head. It also shows that thrombi are dynamic structures in which fibrin can be repeatedly laid down and lysed, observations that are relevant to therapeutic lysis and potential rethrombosis.
Keywords: tPA; uPA; thrombi; fibrinolysis; leucocytes; thrombin